(untitled) (Altre Modernità, 2020)
The present contribution deals with the strategies of selection, which lay at the basis of the so-called national literary canons, by examining a number of critical prose essays written by the American poet Walt Whitman. Under a sociological perspective, Whitman’s essays may be considered not only as mere literary texts, but also as a specimen of meta-literary discourse, fostering the development of the American literary field of the late-Nineteenth century, in its entangled relations with and within the literary marketplace (authors, readers, and publishing industry). Through their publication on the periodical press, Whitman’s essays enact complex strategies of selection, aimed at constructing a national literature by means of references to previous traditions – either by choosing or discarding their aesthetic and ideological paradigms. At the same time, the cultural role performed by magazines and newspapers in post-Civil War America testifies to the double process of legitimization of literary authorship, and commodification of the literary work available to a wide audience mainly made up of middle-class readers.